REMOVAL OF ETHACRIDINE LACTATE FROM AQUEOUS SOLUTIONS ONTO BENTONITE AND ACTIVATED CARBON - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2015)
The adsorption behaviour of ethacridine lactate was studied from aqueous solution onto activated carbon and bentonite under various experimental conditions. The adsorption experiments were carried out at different initial concentrations, pH values and temperatures. Adsorption isotherms have been modeled by Langmuir and Freundlich isotherm equations. It was found that the Langmuir model appears to fit the isotherm data better than the Freundlich model. Thermodynamic parameters were also calculated. The negative value of enthalpy change (Delta B) indicated the exothermic nature of the adsorption process, and the negative values of free energy change (Delta G) were indicative of the spontaneity of the adsorption process.
Keywords: Ethacridine lactate; rivanol; adsorption; bentonite; activated carbon; WASTE-WATER; ADSORPTION; PHARMACEUTICALS; EQUILIBRIUM; RIVANOL; SURFACTANTS; KINETICS; ACID